PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 30 TELUK LANCAR - Abu Samah; Syahrilfudin Syahrilfudin; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to boost student learning outcomes. Low student learning outcomes researcher eager to find a solution to solve these problems, one way is to do research by applying the method of cooperative learning Group Investigation (GI). The type of research is classroom action research (PTK), and carried out in two cycles. While the subject of this study is the fifth grade students of SD Negeri 30 Teluk Lancar. Results from this study is the increase in the activity of the teacher, student activities, and student learning outcomes. At the first meeting of the first cycle, the percentage of teachers activity of 58.33% with enough categories, at the second meeting increased to 70.83% in both categories. At the first meeting of the second cycle of 87.50% the percentage of teachers with very good category, and at the second meeting increased to 95.80% with the category very well. At the student activity also increased, namely in the first cycle of the first meeting of the percentage of 62.50% with a good category, and at the second meeting increased to 75% in both categories. At the first meeting of the second cycle percentage of 87.50% with a very good category, and at the second meeting increased to 91.67% with the category very well. On student learning outcomes also increased with an average score of students before action is 65.95, the first cycle increased to 69.75. And on the second cycle increased again to 75.50.Keywords: Cooperative Learning Model Group Investigation (GI), IPA Learning Outcomes